Technology and the Language Teacher (Arts Faculty Journal, 2012)
Today is the world of Facebook, Twitter, MySpace, Google, Yahoo, I-pods, I- pads. Gadgets reign supreme even in a developing country like Bangladesh (e.g. cell phones) and so technology is fused in every part of our lives, in fact, technology is no longer a tool to create an alternative environment- it is THE environment (Gupta, 2010: 68). Academic institutions are, therefore, expected to prepare students for a technological era that awaits them. As an inevitable consequence, there is an expectation from administrators and students alike that a teacher will use technology to sophisticate teaching. As language teaching professionals our life is also intertwined with technology: for administrative purposes, materials development and storage, grading, professional communication, photocopies, scanning and so on. Technology, whether for the classroom or for official purpose, has to be implemented for its pedagogical value and relevance-not just to jump into the bandwagon. This article is a brief overview of technologies and tools considered necessary for the language teacher of today especially in the context of Bangladesh. It also tries to summarize dominant emerging trends in the field of technology enhanced language learning. DOI: http://dx.doi.org/10.3329/afj.v4i0.12942 The Arts Faculty Journal Vol.4 July 2010-June 2011 pp.206-223